2011
DOI: 10.5344/ajev.2011.10001
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Floor Management Technique on Grapevine Growth, Disease Pressure, and Juice and Wine Composition: A Review

Abstract: Vineyard floor management has multiple goals that encompass improving weed management and soil conservation, reducing soil resource availability to control vine vigor, and influencing desirable aspects in wine quality. This review addresses the effects of cultivation, weed control, cover crops, and mulch on vine growth and balance, disease pressure, yield, and juice and wine quality in many growing regions (Australia, New Zealand, South Africa, Europe, and the western United States); offers recommendations for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
116
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(146 citation statements)
references
References 95 publications
5
116
1
2
Order By: Relevance
“…A recent review by Guerra and Steenwerth (2012) showed how the use of organic mulches increased yields and reduced pathogen and pest pressure. Furthermore, Nguyen et al (2013) showed how natural compost mulch increased grape yield with no adverse effects on grape quality.…”
Section: Mulchingmentioning
confidence: 99%
“…A recent review by Guerra and Steenwerth (2012) showed how the use of organic mulches increased yields and reduced pathogen and pest pressure. Furthermore, Nguyen et al (2013) showed how natural compost mulch increased grape yield with no adverse effects on grape quality.…”
Section: Mulchingmentioning
confidence: 99%
“…shallow-rooted) could help reducing competition with grapevines (Delabays et al, 2006), and largescale commercial availability allows selecting species and cultivars suited to different environments (Pardini et al, 2002). Moreover, choosing sown species can be interesting to reach one or several specific services, such as long-term SOM improvement with grasses, N-fixation or rapid decomposition for N supply using legumes (Guerra and Steenwerth, 2012). Sowing density and spatial structure form levers which can be used to reduce competition with grapevines, or to favour biomass production (Santi et al, 2016).…”
Section: Service Crop Strategy Designmentioning
confidence: 99%
“…The destruction date remains one of the main tactical management levers in vineyards with service crops: in the case of a lack of water early in the season, service crop destruction may stop the transpiration flux and preserve soil water reserves. A short analysis of 10 studies dealing with service crop management issues in a wide range of climates suggests that water availability (represented here as averaged annual rainfall) may be a relevant factor driving service crop destruction or mowing dates in vineyards (Figure 8, see also Guerra and Steenwerth (2012)). …”
Section: Adaptive Strategy and Tactical Managementmentioning
confidence: 99%
“…Moreover, along the trial we noticed herbivore problems with rabbits that showed much higher predilection for the Brachypodium distachyon GC. There are researches who have addressed water competition between the plants of GC and the vines in rainfed Mediterranean vineyards producing grape production decreases (Ruiz-Colmenero et al, 2011;Guerra and Steenwerth, 2012;Muscas et al, 2017). Nevertheless, these types of studies tend to ignore the costs of increasing SOC and erosion reductions on degraded soils.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, GC influences on grape yield is controversial as is affected by many factors (Ripoche et al, 2011 (Pou et al, 2011). Additionally increasing wine quality is often related to GC (Lopes et al, 2011;Guerra and Steenwerth, 2012;Lee and Steenwerth, 2013).…”
Section: Groundcovers: Grape and Winementioning
confidence: 99%